Intimacy and violence: Explaining domestic abuse in lesbian intimate partnerships - Rinaldi, Janna (University of Ottawa (Canada), 2009)
Abstract not available.
Keywords: Philosophy.; GLBT Studies.; Sociology, Individual and Family Studies.